Limitations Of Legal Ability In Dispute Resolution Of Consumer Protection - Tami Rusli (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Consumer Dispute Settlement Board which is expected to be able to provide a fair settlement to thedisputed parties turns out in practice causing confusion for those involved in the implementation processespecially when there is an inclusion of the judiciary role in investigating the case of BPSK rejectiondecision. The problem in this paper is how the limited ability of UUPK law in the consumer disputesresolution is. Based on the result of the study on consumer protection dispute resolution as the end pointof the embodiment of justice, it turns out that the law (legislation) in relation to consumer protection haslimited capabilities so it cannot realize the purpose of the law. The setting of BPSK contained in UUPKand its implementing regulations there are limitations associated with the setting position of the judiciary,the final setting and binding decision so that BPSK in legislation is ambiguous to be called judicial /arbitration because each has its drawbacks